Epidemiology, host range, and associated risk factors of monkeypox: an emerging global public health threat - Ullah, Munib; Li, Yanmin; Munib, Kainat; Zhang, Zhidong (Frontiers in Microbiology, 2023)
Based on recent multiregional epidemiological investigations of Monkeypox (MPX), the World Health Organization on 24th July 2022 declared it a global public health threat. MPX was considered an ignored zoonotic endemic infection to tropical rainforest regions of Western and Central African rural communities until a worldwide epidemic in May 2022 verifies the potential threat of MPXV to be pandemically propagated across the contemporary world using transnational tourism and animal movements to the non-endemic population from endemic one. In 2018-2022, different cases of MPX have been documented in Israel, the United Kingdom, Singapore, and the US from Nigerian travelers. More recently on 27th September 2022, 66,000 MPX cases have been confirmed in more than 100 non-endemic countries with fluctuating epidemiological footprinting from retrospective epidemics. Particular disease-associated risk factors fluctuate among different epidemics. The unpredicted appearance of MPX in a non-endemic globe, suggests some invisible transmission dynamic. Hence, broad-minded and vigilant epidemiological attention to the current MPX epidemic is mandatory. Therefore, the current review came under compilation to highlight the epidemiological dynamic, the global host ranges, and associated risk factors of MPX while concentrating on its epidemic potential and global public health threat.